1993
DOI: 10.1021/bi00073a006
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I-containing lipoproteins, with or without apolipoprotein A-II, as progenitors of pre-.beta. high-density lipoprotein particles

Abstract: Apolipoprotein A-I-(apoA-I-) containing lipoproteins isolated by immunoaffinity chromatography can be divided into two general subfractions on the basis of the presence [Lp(AI + AII)] or absence [Lp(AI - AII)] of apoA-II. The Lp(AI - AII) subfraction can be further subfractionated into two subgroups with pre-beta mobility as well as those of alpha mobility. We have characterized the Lp(AI - AII) and Lp(AI + AII) subfractions after the removal of pre-beta high-density lipoproteins (pre-beta-HDL) to compare only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Whereas some investigators (24) have reported that lipid-poor apoA-I is generated when (A-I/A-II)HDL are isolated from human plasma by immunoaffinity chromatography and incubated with CETP and LDL, others (25) have found this not to be the case. This discrepancy highlights the problems that arise when the HDL from human plasma are used to address questions of this type.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas some investigators (24) have reported that lipid-poor apoA-I is generated when (A-I/A-II)HDL are isolated from human plasma by immunoaffinity chromatography and incubated with CETP and LDL, others (25) have found this not to be the case. This discrepancy highlights the problems that arise when the HDL from human plasma are used to address questions of this type.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, processes catalyzed by hepatic lipase, CETP and PLTP can generate preβ-HDL from α-HDL particles (48)(49)(50)(51)(52). Furthermore, deficiency of apoM inhibits the formation of preβ-HDL (53;54).…”
Section: Discussionmentioning
confidence: 99%
“…The depletion in HDL core in vivo might be explained by two distinct mechanisms: either (i) the net transfer of cholesteryl esters from HDL donors toward lipoprotein acceptors without equimolecular net mass transfer of triglycerides in the opposite direction (10), or (ii) the hepatic lipase-catalyzed hydrolysis of HDL triglycerides initially transferred by CETP (7). In both cases, since the amounts of surface components would remain virtually unchanged, the surface-to-core ratio of HDL would progressively increase, and apoA-I excess would finally dissociate from the HDL surface, leading to the generation of a new HDL product of smaller size (41)(42)(43). As observed in the present study in alcoholic patients undergoing a withdrawal therapy, that latter mechanism might promote in vivo mainly the shift of the plasma HDL 2a subfraction toward the small HDL 3b fraction.…”
Section: Table IVmentioning
confidence: 99%